Pengaruh Service quality Dan Trust Terhadap Customer loyalty Pada Usaha Jasa Titip “Jastip” Di Desa Curahnongko - Wulan Suci Kurnia Sari; Yusita Titi Hapsari; Roro Aditya Novi Wardhani (Siber Nusantara Publisher, 2026)
The purpose of this study was to find out how consumer loyalty to personal shopper services (jastip) in Curahnongko Village is affected by service quality and trust. The study was spurred by the growing number of personal shopper firms, which have emerged as a different way to meet community needs in the face of restricted transit options and an increase in the volume of internet purchasing. This study used a quantitative approach with a survey method. Purposive sampling was utilised to choose 80 respondents who had previously used personal shopper services for the study. Likert-scale questionnaires were used to collect the data, which were then subjected to validity and reliability tests, multiple linear regression, classical assumption tests, partial significance testing (t-test), simultaneous significance testing (F-test), and coefficient of determination analysis using SPSS software. The findings showed that customer loyalty was not considerably impacted by service quality. Nonetheless, client loyalty was positively and statistically significantly impacted by trust. Customer loyalty was found to be highly influenced by both service quality and trust at the same time, accounting for 65.1% of the observed variation. These results showed that the most important element in encouraging client loyalty to personal shopper services in Curahnongko Village was trust.